2018
DOI: 10.1155/2018/4536905
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Patterns ofEscherichia coliin Ethiopia: A Meta-Analysis

Abstract: Background Antimicrobial drug resistance is a global threat for treatment of infectious diseases and costs life and money and threatens health delivery system's effectiveness. The resistance of E. coli to frequently utilized antimicrobial drugs is becoming a major challenge in Ethiopia. However, there is no inclusive countrywide study. Therefore, this study intended to assess the prevalence of E. coli resistance and antimicrobial-specific resistance pattern among E. coli clinical isolates in Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
34
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 57 publications
8
34
3
Order By: Relevance
“…67.4% of E. coli strains examined for this study were resistant to trimethoprimsulfametoxazole. This result is almost similar with 66% of compiled study finding from community settings in South Asia and Sub-Saharan Africa (Ingle et al, 2018) and higher than 57.47% of resistance rate reported from Ethiopia (Tuem et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…67.4% of E. coli strains examined for this study were resistant to trimethoprimsulfametoxazole. This result is almost similar with 66% of compiled study finding from community settings in South Asia and Sub-Saharan Africa (Ingle et al, 2018) and higher than 57.47% of resistance rate reported from Ethiopia (Tuem et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…In Ethiopia, a number of hospital based studies have been conducted on the profile of antimicrobial resistant E. coli isolated from different clinical specimens (Tuem et al, 2018). However, studies from primary healthcare settings are limited.…”
Section: Introductionmentioning
confidence: 99%
“…First, our results revealed that the main carbapenem resistance mechanism of the CR-EC isolates collected in our hospital could be attributed to the productions of carbapenemases and ESBL/AmpC enzymes combined with porin deficiencies. Notably, while NDM-1 subtype was reported to be the most prevalent from previous studies in China (Tuem et al, 2018;Markovska et al, 2019), NDM-5 was observed to be prevalent among the CR-EC isolates. Most importantly, our study revealed that the most prevalent epidemic incompatibility type of the bla NDM−5 -carrying plasmids in our region is IncF (such as IncFIA, IncFIB, and IncFII), which was substantially different from those reported by the other NDM-5 studies (IncA/C and IncX3-type) (Huang et al, 2016;Li et al, 2018), indicating that a new molecular epidemiological CR-EC will be prevalent in China.…”
Section: Discussionmentioning
confidence: 68%
“…Presently, approximately 60,000 people in Europe and United States die each year due to serious infections caused by antimicrobial resistant bacteria (7). The problem is also high in Ethiopia as indicated by few studies (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%